Inflammatory hypotheses of sleep disturbance - depression link: Update and research agenda - Andrea Ballesio (Brain, Behavior, & Immunity - Health, 2023)
Studies in human and experimental animal models support a role of inflammation in the aetiology of depression, yet the precise role played by sleep disturbance (i.e., difficulties falling or maintaining sleep) is poorly understood. Consistent evidence from prospective epidemiological studies suggests sleep disturbance as a predictor of major depression episodes and depression recurrence. In parallel, up to 20% of individuals with sleep disturbance have low-grade peripheral inflammation (i.e., CRP>3 mg/l), and preliminary longitudinal evidence showed that sleep disturbance may even predict the levels of inflammation. Therefore, it is possible that sleep disturbance may increase inflammation, which in turn may contribute (i.e., mediate) to the onset - or worsening - of depression. Alternatively, sleep disturbance may serve as a vulnerability factor and increase the risk of developing depressive symptoms when facing an immune challenge. The aim of this review was to summarise the state of the science on the role of sleep disturbance in contributing to depression-related inflammation. A research agenda is also proposed to advance the study of sleep disturbance in the psychoneuroimmunology of depression.